Removal of heavy metals in green-lipped mussels (Perna Viridis) utilizing edible chelating agents [electronic resource] - Nurul Asma Samsudin, 1987- (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012